Tuberculosis: An Analysis of Mortality Cases in Bandar Lampung City, Indonesia, 2017–2021 - Milu, Sitti Fadhilah; Umanahu, Santri Fitran; Rufianti; Syaqila, Syarifah Aisiyah; Rusmin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Tuberculosis (TB) remains a significant public health concern in Bandar Lampung City. The Case Notification Rate (CNR) fluctuated during 2017–2021, peaking in 2019 and declining sharply in 2020 due to disruptions caused by the COVID-19 pandemic. The proportion of detected TB cases among children was relatively low (35.1%), indicating gaps in contact tracing and early case detection. Furthermore, the treatment success rate for bacteriologically confirmed TB cases in 2021 was only 55.6%, reflecting challenges in treatment adherence and case management. TB-related mortality during treatment reached 65 cases, suggesting issues related to delayed diagnosis and comorbid conditions. These conditions highlight the need to strengthen TB control strategies. Objective: This study aims to describe the distribution of TB mortality in Bandar Lampung City during the 2017–2021 period based on secondary data from the municipal health profile. Methods: A quantitative descriptive design was employed using secondary data from the Bandar Lampung City Health Profile. Data on annual TB mortality were analyzed using tabulation, graphical presentation, and narrative interpretation to identify trends. Results: The findings indicate unstable CNR trends, low pediatric TB detection, suboptimal treatment success rates, and relatively high mortality during treatment. These reflect weaknesses in surveillance, case detection, and patient management. Conclusion: Strengthening surveillance systems, improving healthcare capacity, enhancing early detection, and ensuring equitable health service quality are essential to optimize TB control efforts. Keywords: tuberculosis cases, TB patients, treatment success, TB mortality, Bandar Lampung